Data on cocaine seizures in the western region of Pará from 2018 to 2020 - Soares, Deliane dos Santos; Silva , Flavia Garcez da (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2023)
Objective: this research aims at analyzing the expert reports released by the Scientific Policeof Pará through sociodemographic data, gender and amount of cocaine received by the PublicSecurity agency in the period from 2018 to 2020 regarding seizures in the municipality ofSantarém/PA and adjacent cities. Methodology: this research is an exploratory and descriptivestudy with data validated in definitive expert reports of chemical analysis, performed on cocainesamples from seizures by police agencies in the state of Pará. Results: a total of 1,280 definitiveexpert reports with positive results for cocaine were consulted. With this, there was prevalence ofmales in involvement with trafficking; regarding schooling levels and age groups, this informationwas missing from the reports; in relation to seized cocaine there is growth in trafficking in 2019,with Santarém as the central city for trafficking in this region. Conclusion: the cocaine quantifiedin this study shows that, during the three years of analysis of data from the Scientific Police ofPará, a reasonable number of seized cocaine was noticed, not only in the city of Santarém, butalso in adjacent cities, indicating active circulation of this substance in the western region ofPará, also pointing to male presence, mostly, in trafficking of this substance.